Self-Efficacy, Anxiety, and Emotional Intelligence: Do They Contribute to Speaking Performance? - Masrifatul Afifah; Ary Setya Budhi Ningrum; Sri Wahyuni; Burhanudin Syaifulloh (Journal of Languages and Language Teaching, 2024)
Speaking demands self-confidence and composure when dealing with other people. Furthermore, communicating in English is a big barrier for many students due to self-efficacy, anxiety, and emotional intelligence. This study examined direct and indirect variable contributions. This path analysis study used multiple regression and mediated model. This study involved 128 of the tenth graders students at SMA Senopati, Sidoarjo. To collect the data, the instruments used a closed-ended questionnaire about self-efficacy, anxiety, emotional intelligence and speaking test. This study yielded seven conclusions. First, self-efficacy had a weak effect on speaking performance (estimate =.128, p-value.000). The estimate value of.506, p-value.001, showed that self-efficacy contributes significantly to emotional intelligence. Anxiety's contribution to emotional intelligence was minimal (estimate value -.397, p-value.005). The fourth finding showed that anxiety directly affects speaking performance (estimate value -.069), p-value.000. The fifth finding showed that emotional intelligence had a weak effect on speaking performance (estimate value.034, p-value.004). Significant indirect influence of self-efficacy through emotional intelligence on speaking performance (Sobel test=2.1220>1.96, p-value 0.033<.05). Anxiety indirectly affects speaking performance through emotional intelligence (Sobel test=-.2.0043>1.96, p-value 0.045<.05).